The health-related quality of life for hemiarthroplasty and total hip arthroplasty in the elderly: A meta-analysis - Su, Yaping; Li, Ruiling; Ren, Xiangying; Wang, Yuanyuan; Bai, Xiaolu; Zhang, Yurui; Han, Lingyu; Wang, Yiman; Liang, Ran (Frontiers in Medicine, 2023)
Purpose What constitutes the optimal surgical plan for femoral neck fractures (FNFs) in elderly patients is controversial. The European quality of life 5-Dimension Questionnaire (EU-5Q) is an international scale used to measure the health-related quality of life (HRQoL) after surgery. We aim to verify the hip arthroplasty effect in elderly patients by analyzing HRQoL scores in the EU-5Q scale. Methods We searched the EBSCO, Embase, PubMed, Ovid, Cochrane Library, and Web of Science databases using strict searching from established to 30 November 2022; used the Cochrane Library's Risk of Bias Assessment Tool and the Newcastle–Ottawa Scale to evaluate the literature; and used RevMan5.4.1 software to perform a meta-analysis. All the included studies used the EU-5Q scale to validate the overall outcomes for elderly hip arthroplasty. Results The final included literature is composed of four RCTs, two cohort studies, three case–control trials, and three cross-sectional surveys. This study compared HRQoL scores measured by the EU-5Q scale, including 328 elderly patients with total hip arthroplasty (THA) and 323 elderly patients with hemiarthroplasty, which is statistically significant (OR = 0.05; 95% CI, 0.02 0.08; P = 0.002). The subgroups were as follows: unipolar vs. bipolar and cemented vs. uncemented hemiarthroplasty (OR = 0.06; 95% CI, 0.03 0.08; P < 0.001), follow-up time and age arthroplasty (OR = 0.16; 95% CI, 0.11 0.22; P < 0.001), molecular exercise and enhanced recovery after surgery (ERAS) (OR = 0.02; 95% CI,−0.03 0.07; P = 0.38), and analysis of hemiarthroplasty with cognitive dysfunction vs. the normal group (OR = 0.17; 95% CI, 0.08 0.26; P < 0.001). The outcome analysis was consistent with the included studies, and HRQoL of the EU-5Q scale is sensitive to surgical outcomes between THA and hemiarthroplasty. Conclusion Surgeons still need to further evaluate and verify whether the hip arthroplasty surgical program or effect in elderly patients is optimal. Hemiarthroplasty operations in elderly patients have pointed toward a new direction for clinical treatment, and HRQoL scores measured by the EU-5Q can sensitively reflect the rehabilitation status after hip arthroplasty surgery. Moreover, the extensive correlation between surgical outcomes and perioperative neurocognitive function should be further investigated.